Counteraction to Illegal Drug Trafficking Using the Internet: Modern Problems and Contradictions - SIDOROV, Anatoly S. (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017, 2017)
General characteristics of crimes related to illicit trafficking in drugs using the mass media or electronic or information and telecommunication networks, including the Internet network are presented. The main problems of detection and suppression of this type of crimes are considered, as well as the main contradictions in the international legal regulation of interaction issues between law enforcement agencies of various states that impede effective counteraction to drug traffic. In the course of the study, the state of regulatory and legal regulation of issues related to countering crimes related to illicit trafficking in narcotic drugs with electronic and information and telecommunication networks, including the Internet network, in the Russian Federation was analyzed. International cooperation in this field was assessed. The practice of investigating and prosecuting criminal cases related to drug trafficking has been studied.